Essence and State of the Public Transport Planning and Management Systems in the City of Sofia - Petrov, Emil (Research Papers, 2019)
Implementation and development of ITS solutions in the field of transport planning and management is important for the normal functioning of the city in which more than 17.5% of the population of the country live and work. The opportunity for collecting data from various sources in real time, its processing and analysis, provide a powerful tool in the hands of the government for maintaining this important service of the city.